Associations between immunologically - related genetic polymorphisms and cytokines expression on human leptospirosis susceptibility and severity - Wan Yusoff, Wan Shahriman Yushdie (2021)
Leptospirosis is a zoonotic disease caused by spirochetes species of the genus Leptospira. Despite being the common causes of zoonotic morbidity worldwide, there is still a knowledge gap between leptospiral pathogenesis and human immune responses. This study aimed to explore the impact of selected immune parameters on leptospirosis susceptibility and severity. A prospective study was conducted among clinically-suspected leptospirosis cases admitted to hospitals in the south-central region of Malaysia (January 2016–December 2017). Of 132 clinically suspected leptospirosis patients samples collected, 94 were confirmed-leptospirosis. The study included 19 healthy controls. Gene polymorphisms for human leucocyte antigen (HLA) were determined using a sequence-specific oligonucleotide (SSO) probe for Malay subjects. Cytokine levels were quantified using a Simple Plex™. Immunophenotyping of T cells was performed using a flow cytometer. Single nucleotide polymorphism (SNP) studies for selected cytokines genes were performed using the BGISEQ sequencing platforms. When comparing fatal to non-fatal, laboratory investigation found that fatal cases had significantly higher blood urea nitrogen (BUN) and serum creatinine. Genotyping study of HLA revealed HLA-A*02, -A*23, -A*33, -B*15, -C*03, and -DRB1*16 alleles were significantly associated with leptospirosis susceptibility, while -DQB1*03 was significantly associated with less susceptibility to the disease. Furthermore, HLA-A*33 was significantly associated with severe leptospirosis, while HLA-C*03 was significantly associated with renal involvement. This study found a statistically significant association concerning severe cases for gene SNP IL-33 (rs1854709). In contrast, single nucleotide insertions and deletions (INDELs) in gene IL-18 (rs10642361) and IL-8 (rs2227541) were associated with mild disease. IL-6, IL-17A, IL-22, and IL-8 levels were significantly higher in fatal than non-fatal cases. These findings confirm that the host immune response influenced disease severity, indicating the significant associations between pro-inflammatory cytokines and chemokines in fatal cases. The importance of IL-8 was further supported by IL-8 SNP (rs2227541) in mild cases. Th1 cells were significantly lower among leptospirosis patients than in healthy controls. Several HLA alleles were related to disease susceptibility and protection from leptospirosis. This study allowed a better understanding of the important role of the host immune-related biomarkers in the clinical outcome of leptospirosis infection. It may be useful in developing early prognostic and selective immunotherapy for the disease.